Predictors of Hypertension among Adult Female Population in Kpone-Katamanso District, Ghana - Kwabena Acheampong; Jackim M. Nyamari; Daniel Ganu; Stella Appiah; Xiongfeng Pan; Atipatsa Kaminga; Aizhong Liu (International Journal of Hypertension)
Background. Hypertension is an independent risk factor of cardiovascular disease, which is one of the biggest health challenges today. The objective of this study was to estimate the prevalence of the problem and other factors related to hypertension among women who are 25 years and above. Methods. A community-based cross-sectional study was conducted from September and November 2017. A multistage cluster sampling technique was used to select the study participants. The data was collected using a structured questionnaire and physical measurements adapted from “WHO STEPwise approach to chronic disease risk factor surveillance (STEPS).” Data were examined using the SPSS program IBM version 20. Descriptive statistics, including proportions, frequencies, and cross-tabulations, were used to summarize the study variables. A binary logistic regression was fitted variable with a p value of < 0.7. The bivariable analyses were entered in the multivariable analysis to control the possible effect of confounders. Multivariable logistic regression analysis was used to identify factors associated with hypertension. The Adjusted Odds Ratio (AOR) with a 95 % Confidence Interval (CI) was computed to show the level of certainty. A p value of <0.05 was considered statistically significant. Results. The study indicated that the prevalence of hypertension (BP ≥ 140/90 mmHg) was 33.8% (95% CI 27.4-40.2) which increased with age. At the time of the study, women aged 45-64 years [AOR =2.19, (95% CI: 1.11-4.34, p<0.02)] and 65+ years [AOR =5.13, (95% CI: 2.20-11.99), p<0.001] were two to five times as likely as those with age of 25-44 years to be hypertensive. Women who had a higher body mass index (BMI) ≥30 kg/m2 were two times as likely as those with normal weight to be hypertensive [AOR 2.38, (95% CI; 1.14-4.95, p<0.02)]. Women who did not consume fresh fruit daily were three times as likely as those women who consume fresh fruit daily to be hypertensive [AOR 3.17 (95% CI; 1.05-9.55, p<0.04)]. Conclusion. Increasing age, obesity, and women who did not consume fresh fruits daily were associated with hypertension, indicating opportunities for health education and other prevention measures.